Model-Driven Development for Spring Boot Microservices - Mendonça, Bruno Costa (2021)
As microservices become more and more common, there is more interest in optimizing their development, making it faster, reducing the complexity and making it less error and bug prone. This work aims to explore how Model-driven Engineering (MDE) can be used to aid microservices’ development, especially Java microservices using Spring Boot. Firstly, this work starts by presenting its context, with a brief introduction to MDE and microservices, and how MDE can be used to facilitate microservices’ development. Then the State of the Art presents MDE base technologies and MDE-based solutions that can be used to develop microservices. Furthermore, a value analysis was also done, to explore the benefits of using MDE, and to define its value proposition. Lastly, a case study was elaborated following three different approaches, traditional development, DSL-based approach, and MDE-based tool approach, which were then compared by code quality and time required for development of the microservices. This work is especially interesting for someone who wants to develop Java microservices and wants to explore the different approaches and technologies to do so, namely by using MDE.